Research study on virtual agent technology / Khairul Izadieffendie Borhan - Borhan, Khairul Izadieffendie (2004)
Nowadays, virtual agent has become a new paradigm for developing software application. It is now being used in an increasingly wide variety of applications ranging from comparatively small systems until complex and critical system. This research basically discusses several features such as evolutionary, behaviors and characters, advantages, challenges and solution for virtual agent processes of development. The information gathered during this research was obtained from various resources that includes online and offline resources, observation of the current technology and data analysis that is used to analyze the collected resources. The findings of this research will explain in details to the readers about virtual agent concept The main objective of this research is to help the readers to understand why virtual agent technology is seen as a new important tool for building wide array systems. A future works might include developing a virtual agent with the entire strength feature or enhancement of current virtual agent to solve the weaknesses